Education in Pediatrics Across the Continuum (EPAC): First Steps Toward Realizing the Dream of Competency-Based Education. (March 2018) - Andrews, John S.; Bale, James F.; Soep, Jennifer B.; Long, Michele; Carraccio, Carol; Englander, Robert; Powell, Deborah
Abstract : The Education in Pediatrics Across the Continuum (EPAC) Study Group is developing the first competency-based, time-variable progression from undergraduate medical education (UME) to graduate medical education (GME) in the history of medical education in the United States. EPAC, an innovation project sponsored by the Association of American Medical Colleges and supported by the Josiah Macy Jr. Foundation, was developed through a collaboration between five medical schools and multiple professional organizations with an interest in undergraduate and graduate medical education. The planning and implementation process demanded cooperatively addressing practical barriers such as education requirements for licensure and developing approaches to learner assessment that provided meaningful information about competency. Each participating school now has at least three cohorts of learners participating, and the program is transitioning its first cohort of students from UME to GME based on achievement of predetermined competencies that allow this transition. Members of the first cohort of learners in this program have begun their pediatric residency training at different times beginning in late 2016, confirming the feasibility of competency-based advancement from UME to GME in pediatrics. Although there is still much to learn about the outcomes of EPAC learners' professional development in residency training and beyond, EPAC has defined an operational approach to a different path through medical school and into residency training, based on the attainment of competence.